A corrective solution for finding the effects of edge-rounding on complete contact between elastically similar bodies. Part II: Near-edge asymptotes and the effect of shear. (15th May 2016) - Fleury, R.M.N.; Hills, D.A.; Barber, J.R.
Abstract: This paper is the second part of a new approach to introduce edge rounding into elastic flat punch solutions. Building on the concept developed in the first paper of using a three-quarter plane as an asymptote to the finite punch with rounded edge problem, we now move the observation point to the very edge of the contact and introduce asymptotes for the local contact tractions so that shear may be included in the analysis to solve the partial slip problem. The edge asymptotes are used to obtain the slip zone size and the normal and tangential contact traction distribution, where the rounded edge in contact can be reasonably approximated by a half-plane.